Synthesis, antimicrobial evaluation and QSAR studies of N'-benzylidene/(1-phenylethylidene)undec-10-enehydrazides - Shashi Kumar, Rakesh Narang, Surendra Kumar Nayak, Sachin Kumar Singh, Balasubramanian Narasimhan (Journal of Applied Pharmaceutical Science, 2016)
A series of N'-benzylidene/(1-phenylethylidene)undec-10-enehydrazide was synthesized starting from undec-2-enoic acid through multi-step reactions. Synthesized derivatives were evaluated for their in vitro antimicrobial activities against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Aspergillus niger and Candida albicans by tube dilution method. The preliminary results showed the significance of o-NO2, m-NO2 and m-OCH3 groups at phenyl ring in describing antimicrobial activity of synthesized compounds. QSAR studies revealed that second order molecular connectivity index (2χ) and Balaban topological index (J) are the key parameters for antimicrobial activity of synthesized hydrazide derivatives and can be cosidered as important factors for interaction with target site of different microorganisms. It is pertinent to note that multi-target QSAR models were more significant in demonstrating the antimicrobial activity than one-target QSAR models.
Keywords: Antifungal, antibacterial, undec-10-enoic acid, hydrazide, QSAR.